ТАРИЙХ ПӘНИН ОҚЫТЫЎДА КӨРГИЗБЕЛИЛИК МЕТОДЫНАН ПАЙДАЛАНЫЎ МӘСЕЛЕЛЕРИ (Сүўретлеў көргизбелилиги мысалында) - Баўетдинов, Р.; Ганиев, Т. (SCIENCE and SOCIETY, 2017)
The article deals with the questions of effective use of the method of presentation. The author gives the analysis to kinds and methods of using visual aids. It is emphasized the positive influence of presentation in increasing the quality and productivity of a lesson.